Study on college students' motivation to participate in Taijiquan and its influencing factors - Pang, Bo; Jiang, Jinli; Wang, Hanyu; Qu, Guofeng; Zhu, Hongbo (The Journal of the International Society of Chinese Health Practices, 2021)
See PDF for details